Analisis Kepatuhan Karyawan Pada PT. XYZ - Sahry, Adelia Azahra; Wolor, Christian Wiradendi; Marsofiyati, Marsofiyati (Journal of Student Development Informatics Management (JoSDIM), 2023)
Compliance means obeying and liking to obey important human resource rules, because the more obedient employees are to the company, the higher the work performance they can achieve. Work loyalty, apart from work discipline/obedience, is very important for managing human resources in a company. Work loyalty can be defined as loyalty, devotion and trust given or shown to the company; This creates a sense of ownership and strives to provide the best behaviour and service. This research involved 38 permanent employees of PT XYZ and aims to find out how compliance with loyalty impacts their work performance. All employees of PT XYZ were used as subjects of this research to see how compliance at work, work environment and work culture influence company performance. The research results show that compliance greatly influences the performance of PT XYZ employees, and work culture also has a positive influence on their performance. Apart from that, compliance, work environment and overall work culture have a positive effect on the performance of PT XYZ employees. Employee compliance analysis can help management identify areas where improvement is needed. If there is low compliance with a particular policy or regulation, corrective action may be taken, such as additional employee training, increased communication to employees, or stricter enforcement of the rules. An effective compliance analysis can help organizations prevent legal issues, promote a company culture of integrity, and create a safe and efficient work environment. Apart from that, compliance analysis can also help in building a good reputation in the eyes of shareholders and customers.